EVALUATION OF CLINICAL ASPECTS RELATED TO LOWER LIMB AMPUTATION AMONG INDIVIDUALS LIVING WITH TYPE 2 DIABETES MELLITUS IN MEXICO: EVALUACIÓN DE ASPECTOS CLÍNICOS RELACIONADOS CON LA AMPUTACIÓN DE MIEMBROS INFERIORES EN PERSONAS QUE VIVEN CON DIABETES MELLITUS TIPO 2 EN MÉXICO - Parra Acosta, Julio Cesar (2024)
Introduction: Diabetes continues to be one of the leading causes of disability and death in the global population. It is estimated that approximately 25% of people living with diabetes will develop an ulcer on one of their lower pelvic limbs. Objective: The present study evaluates the clinical aspects related to lower pelvic limb amputation in a cohort of patients with diabetes mellitus. Materials and Methods: A retrospective cross-sectional study was conducted consisting in a review of the total census of patients with type 2 diabetes. They received medical attention in the setting of the study in the period January-May 2022. According to the ICD-10 a total of 2021 patients with multiple complications of diabetes were identified through their clinical records. One hundred patients were diagnosed with diabetic foot. Results: Degree of average glycemic control in the 6 months following diagnosis of diabetic foot was a relevant variable. Since patients with optimal glycemic control by quantifying their fasting glucose levels (<130 mg/dl) as well as their glycated hemoglobin values (< 7%), had a less frequency of amputations (p˂0.001; Chi2) compared to those patients without an adequate glycemic control. Conclusions: After the analysis conducted in the population, it was found that being male, having glycated hemoglobin values higher than 7%, and having average fasting glucose values higher than 130 mg/L increase the probability of presenting a lower extremity amputation.